The Flawed Representation of the Dalit In Mulk Raj Anand’S Untouchable: The Persistent Struggle for Dalit Liberation in Mulk Raj Anand’s Untouchable (Journal of Advances and Scholarly Researches in Allied Education, 2013)
“There have been many Mahatmas in India whose sole objectwas to remove Untouchability and to elevate and absorb the Depressed Classes,but every one of them has failed in his mission. Mahatmas have come andMahatmas have gone. But the Untouchables have remained as Untouchables.”